(untitled) (Medico Legal Update, 2020)
The current research aims to building proposed standards to evaluate the performance of teachers of the Arabic language male and female teachers in according to the quality systems of modern education and according to the following areas: ((Planning, learning strategies, scientific material, assessment, teacher’s profession)),The number of standards (16) criteria and the number of indicators (72) and I developed for each paragraph five alternatives (Excellence, very good, good, average, acceptable), and verified the validity of the tool and its stability, which has been applied by the researcher on a sample of teachers and teachers of the language in the center of the province numbered (193) male and female, the researcher found that the performance of teachers both gender was generally positive which calls for more attention to the preparation and training of teachers according to quality performance standards.